The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/rda.12736
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of matrix metalloproteinases changes during folliculogenesis in the cat ovary

Abstract: Matrix metalloproteinase (MMP) has been implicated as having roles in ovarian folliculogenesis. Here, we determined the expression pattern of six MMPs (MMP1, MMP2, MMP3, MMP7, MMP9 and MMP13) and their endogenous tissue inhibitor, TIMP1, during cat follicle growth. Different developmental stage follicles were mechanically isolated and gene expression analysed by real-time qPCR while MMP1, 2, 9 and 13 localization was determined by immunohistochemistry. With the exception of MMP13, the amount of MMP mRNA was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…The following primers for feline cMyc were designed based on the gene sequence previously published: cMyc-FW: 5 ′ -CAAAAGGTCGGAATCGGGGT-3 ′ , cMyc-REV: 5 ′ -CGTGGCATCTCTTAAGGACCA-3 ′ (33). Feline MMP-1, MMP-2, and MMP-9 genes were amplified by using the primers described previously (34)(35)(36). Amplification of feline β-2-microglobulin (β2MG) was performed in parallel to allow normalization of the results as previously reported (37).…”
Section: Rna Extraction Reverse Transcription (Rt) and Real-time Qumentioning
confidence: 99%
“…The following primers for feline cMyc were designed based on the gene sequence previously published: cMyc-FW: 5 ′ -CAAAAGGTCGGAATCGGGGT-3 ′ , cMyc-REV: 5 ′ -CGTGGCATCTCTTAAGGACCA-3 ′ (33). Feline MMP-1, MMP-2, and MMP-9 genes were amplified by using the primers described previously (34)(35)(36). Amplification of feline β-2-microglobulin (β2MG) was performed in parallel to allow normalization of the results as previously reported (37).…”
Section: Rna Extraction Reverse Transcription (Rt) and Real-time Qumentioning
confidence: 99%
“…The MMP family belongs to zinc‐ and calcium‐dependent metalloproteinases and encompasses at least 28 members that can be subdivided into four broad classes: collagenases, gelatinases, stromelysins, and membrane‐type MMPs . Several members of the MMP family (e.g., MMP1, MMP2, MMP7, MMP9, and MMP13) are expressed in mammalian ovarian follicles at different developmental stages, and the expression of these MMPs is highly regulated in response to gonadotropins, sex hormones, and growth factors . For instance, MMP1 and MMP9 are expressed in granulosa cells at all follicular stages, and MMP2 is expressed in the granulosa/cumulus cells of early and antral follicles .…”
Section: Introductionmentioning
confidence: 99%
“…Several members of the MMP family (e.g., MMP1, MMP2, MMP7, MMP9, and MMP13) are expressed in mammalian ovarian follicles at different developmental stages, and the expression of these MMPs is highly regulated in response to gonadotropins, sex hormones, and growth factors . For instance, MMP1 and MMP9 are expressed in granulosa cells at all follicular stages, and MMP2 is expressed in the granulosa/cumulus cells of early and antral follicles . A recent study performed using clinical samples showed that MMP2 and MMP9 are present in follicular fluid and that MMP2 activity is positively correlated with oocyte and embryo quality .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the biological analysis showed that the differentially expressed genes (DEGs) which were enriched in the PPAR signalling pathway included matrix metalloproteinase 13 (MMP13), which upregulated at 65 dpf and 180 dpf, but downregulated at 600 dpf. MMP13 is mainly expressed in the primary follicles and plays an important role in follicle development along with MMP1 (Fujihara et al, 2016). The study found that PLIN1 was speci cally expressed in the testis and its mRNA level decreased signi cantly with development, which was con rmed to play an important role in the early stage of the rst meiosis of spermatogenesis (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%